“THE BOOK AS A WORLD”: MITKO MADZUNKOV'S LITERARY ONTOSTRATEGIES (PALIMPSEST / ПАЛИМПСЕСТ, 2022)
Starting from the theoretical premises for the ontological dominant of postmodernist prose, the text aims to interpret the manifestations of this dominant in the Mitko Madzhunkov's novels: Времето на ирвасите, Птиците од ланските гнезда и Правта на библиотеките. The interpretive focus is placed on two levels: first, on the interpretation of the repertoire of ontological themes that are articulated in the novels, mainly related to the games between the texts and the worlds projected in them; second, on the interpretation of the repertoire of procedures (metafictional and intertextual) by which those themes are placed in the foreground in the novels.Keywords: ontological dominant; postmodernist novel; metafiction; intertextuality.